Sportscape features and team quality : implications on spectators satisfaction and future attendance. - Yusof, Aminuddin; Lee, Hooi See (2008)
The purpose of this study was to examine the relationship between stadium factors (sportscape) and team quality on spectators’ satisfaction and their intentions to attend soccer matches in Malaysia. The subjects comprised of 371 spectators attending a Malaysian Super League soccer match. The subjects completed the sportscape instrument (Wakefield, Blodgett, & Sloan, 1996) to measure perceptions of the physical facility while the quality of the team was measured using items from Zhang, Pease, Smith, Lee and Lam (1997) scale. Multiple linear regression analysis revealed that team quality and sportscape variables together predicted spectators’ satisfaction (R² = 0.289, adjusted R² = 0.285) and their intentions to attend future matches (R² = 0.278, adjusted R² = 0.274). The results of the study were discussed in light of earlier findings concerning sportscape features and team quality. Practical implications of the results of the study to facility managers and sport marketers were also discussed.